K+ channel blockade limits AF and suppresses phase 3 EADs by slowing repolarization in an electromechanical cell computational model - Mazhar, Fazeelat; Severi, Stefano; Bartolucci, Chiara (Frontiers in Physiology, 2026)
PurposeSelective inhibition of atrial proarrhythmicity can be therapeutic for reducing the atrial fibrillation (AF) burden. Atrial-selective K+-channel blockade (mainly Kv1.5 and Kv4.3 channels conducting the sustained IKur and transient Ito outward currents) promises to suppress AF with a favorable benefit-to-harm ratio. The mechanisms underlying the efficacy of K+ channel blockade under arrhythmic conditions and its association with electrophysiological and contractile remodeling in AF remain to be investigated.MethodsUsing our electromechanically coupled model MBS2023, we have simulated the effects of 4-aminopyridine (4-AP) and AVE0118 at different basic cycle lengths (2–0.25s). We have dissociated the primary and secondary responses to determine the drug’s underlying mechanisms of action. We have analyzed the effects of K+-channel blockers under arrhythmogenic conditions induced by either forward excitation-contraction coupling (ECC) or mechano-calcium feedback.ResultsAt the basal rate, the voltage-mediated increase in IKr induced by 4-AP shortens the action potential duration (APD) under sinus rhythm (SR), whereas a surge in ICaL prolongs APD under AF. 4-AP can exacerbate the vulnerability to phase 2 early afterdepolarizations (EADs) by slowing repolarization and prolonging myofilament activation. K+-channel blockade can decimate the susceptibility of delayed afterdepolarizations (DADs) by eliminating the cytosolic Ca2+ overload. The slowing of repolarization induced by 4-AP can suppress the reopening of Na+ channels during phase 3 EADs.ConclusionIn both types of EAD, a shorter, Ca2+-desensitized sarcomere can reduce the propensity for AF in the model. In general, K+ channel blockade has anti-arrhythmic potential to suppress phase 3 EADs by slowing repolarization.